Quantifying Domestic Violence in Times of Crisis - Dan Anderberg; Helmut Rainer; Fabian Siuda (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We propose a model that (i) provides an algorithm for measuring temporal variation in domestic violence incidence based on internet search activity and (ii) makes precise the conditions under which this measure yields less biased estimates of the domestic violence problem during periods of crisis than traditional, police-recorded crime measures. Analyzing the COVID-19 lockdown in Greater London, we find a 40 percent peak increase in our internet search-based domestic violence index, 7-8 times larger than the increase in police recorded crimes and much closer to the increase reported by victim support charities in relation to helpline calls.
Keywords: J12; I18; 330; COVID-19; domestic violence; police-recorded crime; internet search data; signal-to-noise